2021
DOI: 10.1007/s00278-021-00546-x
|View full text |Cite
|
Sign up to set email alerts
|

Gemeinsame Grundlage von Alexithymie und expressiver Suppression

Abstract: Zusammenfassung Hintergrund Internationale Studien konnten bereits einen Zusammenhang zwischen Alexithymie und expressiver Suppression belegen. Im deutschsprachigen Raum wurde dieser Zusammenhang bisher nur sehr selten betrachtet. Übergeordnetes Ziel der vorliegenden Studie war die Untersuchung eines korrelativen und faktoriellen Zusammenhangs von Alexithymie und expressiver Suppression. Material und Methoden Insgesamt 317 Personen nahmen ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A positive or negative correlation between the scales of the ERQ (Abler & Kessler, 2009 ) and measurement procedures of the Toronto model of alexithymia (Taylor et al, 1997 ) has already been established several times (cf. Schiewer et al, 2022 ). In this case, the correlation would only confirm already recorded relationships between the concepts of expressive suppression and alexithymia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A positive or negative correlation between the scales of the ERQ (Abler & Kessler, 2009 ) and measurement procedures of the Toronto model of alexithymia (Taylor et al, 1997 ) has already been established several times (cf. Schiewer et al, 2022 ). In this case, the correlation would only confirm already recorded relationships between the concepts of expressive suppression and alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the final extracted scales of the KFS were correlated with the sub- and total scales of the TAS-26 (Kupfer et al, 2001 ) and the ERQ (Abler & Kessler, 2009 ). Since a development of the items was semantically close to these two survey instruments, as well as the results around Schiewer et al ( 2022 ) showed a correlative and factorial relationship of both theoretical concepts measured by the constructs of the TAS-26 (Kupfer et al, 2001 ) and the ERQ (Abler & Kessler, 2009 ), a high correlation to both instruments was aimed for.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations